Makers - Doctorow, Cory. (New York Tom Doherty Associates, 2009)
What happens to America when two geeks working from a garage invent easy 3D printing, a cure for obesity, and crowd-sourced theme parks? Lawsuits against Disney are only the beginning in this major novel of the booms, busts, and further booms in store for America in the age of open source and its hero/hacker culture.
A Tom Doherty Associates Book.
Keywords: Inventors -- Fiction; Businesspeople -- Fiction; Technology -- Fiction; Science fiction